Effectiveness of Civil Servant Investigators in Enforcing Regional Regulations in West Sulawesi Province - Aksan, ‎; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
This research aims to analyze the effectiveness of civil servant investigators (PPNS) in enforcing regional regulations in West Sulawesi Province. Regional regulations (Perda) have an important role in regulating the administration of regional government and community life. PPNS acts as a law enforcement apparatus with the authority to investigate and prosecute violations of regional regulations. This research uses a literature review method by comparing various research results related to the effectiveness of PPNS in enforcing regional law. The results of the research show that the effectiveness of PPNS is influenced by several factors, including the capacity and competence of investigators, independence in carrying out tasks, and adequate support for facilities and infrastructure. In addition, coordination between related institutions is also an important element in creating an effective law enforcement system. However, the main challenges faced by PPNS in West Sulawesi Province are limited resources, both in terms of personnel and operational budget. In addition, the lack of public understanding of regional regulations also hinders the effectiveness of law enforcement. To increase the effectiveness of regional regulation enforcement, it is necessary to have a strategy to improve the capacity of PPNS through continuous training, as well as increased coordination between institutions and legal socialization to the community.